VAGINAL CUFF DEHISCENCE AFTER TOTAL LAPAROSCOPIC HYSTERECTOMY: PROSPECTIVE COMPARISON OF TWO TYPES OF SUTURING TECHNIQUES - Dojki, Samina Saleem; Alia Bano; Saliha Kanwal (Journal of Ayub Medical College Abbottabad, 2023)
Background: To compare the frequency of vaginal cuff dehiscence after total laparoscopic hysterectomy between two different suturing techniques. Place and duration of study: The study was conducted at three centers; postgraduate tertiary care hospital, university affiliated hospital and private multidisciplinary hospital. The studied duration was from January 2019 to June 2020. Method: All patients with indication of total laparoscopic hysterectomy during the study period were included. These were randomly divided in to two groups A and B. Group A was performed upon the conventional interrupted figure of 8 vault suturing and group B with continuous, running, double layered suturing. Keeping the demographics almost same the frequency of a known but rare complication of vaginal cuff dehiscence (VCD) was determined. Results: A total of 195 patients were enrolled. Of these 87 were in group A and 108 in group B. The results were unequivocal as only one patient had the said complication. Conclusion: The morbid complication has no relation with the technique of vault suturing.